POSHAN’s abstract digest on maternal and child nutrition research - Issue 42 - Avula, Rasmi (International Food Policy Research Institute, 2021)
In this 42nd issue of the POSHAN Abstract Digest, we bring to you a collection of interesting articles on various topics pertaining to maternal and child nutrition, impact of COVID-19 on food insecurity, as well as modeling and experimental studies. This issue features studies on gaps in maternal diets, the role of complementary feeding in high child malnutrition rates, the importance of animal source foods for linear growth, maternal mental health and its relationship with child undernutrition. Two validation studies, one focused on validating a novel diet quality score in southern India, and one that validates a new indicator to measure coverage of quality of antenatal care, are also included.